Chromosome evolution and phylogeny in Ronderosia (Orthoptera, Acrididae, Melanoplinae): clues of survivors to the challenge of sympatry?. (13th August 2018) - Castillo, Elio R.D.; Martí, Dardo A.; Maronna, Maximiliano M.; Scattolini, María C.; Cabral‐de‐Mello, Diogo C.; Cigliano, María M.
Abstract: In an attempt to unveil the origin of neo‐sex chromosomes in Ronderosia Cigliano grasshoppers, we performed a combined phylogenetic analysis based on morphological (external morphology and male genitalia) and molecular data (COI, COII, 16S and ITS2) to explore the chromosome evolution within the genus. We also analysed the distributional patterns of the various Ronderosia species and considered the possible role of chromosome rearrangements (CRs) in speciation processes within the genus in the light of 'suppressed‐recombination' models. We mapped the states of three chromosomal characters on the combined tree topology. The combined evidence supported Ronderosia as a monophyletic group. The cytogenetic analyses of the genus demonstrated the importance of rearranged karyotypes with single, complex and multiples neo‐sex chromosome determination systems in all species. The chromosome character optimisation suggests X‐autosome centric fusion as the mechanism responsible for neo‐sex chromosome formation in most Ronderosia species, except in R. dubia and R. bergii . Similar autosomes were involved in fusions with the ancestral X chromosome in Ronderosia, supporting previous hypotheses on the unique origin of X‐autosome fusion for the sex chromosome in the genus. As a source of chromosome variation, autosome‐autosome centric fusion played a secondary role in Ronderosia compared with other Dichroplini. Given the homogeneity in the morphological features, the sympatric distribution of closely related species and the intrinsic property of centric fusion as suppressors of the crossing over, we suggest that CRs may have played a key role during the speciation process within Ronderosia . Abstract : We performed a combined phylogenetic analysis based on morphological and molecular data (COI, COII, 16S and ITS2) to explore the chromosome evolution within Ronderosia . We also analysed the distributional patterns of the various Ronderosia species and considered the possible role of chromosome rearrangements (CRs) in speciation processes within the genus. The combined evidence supported Ronderosia as a monophyletic group. The cytogenetic analyses evidenced rearranged karyotypes with single, complex and multiple neo‐sex chromosome determination systems in all species. Given the homogeneity in the morphological features, the sympatric distribution of closely related species and the intrinsic property of centric fusion as suppressors of the crossing over, we suggest that CRs may have played a key role during the speciation process within Ronderosia .